EDITORIAL: A better media deal? - Charu Uppal (Asia Pacific Network, 2007)
As this edition of Pacific Journalism Review went to press, Fiji was in the throes of conducting a census. Technology is helping the process. Technology is often associated with democratising the political proc- ess, decentralising the status quo, upholding free speech, promoting direct democracy and amplifying voices that often remain silent. Regardless of the potential of technology to deliver these freedoms, the issues that existed before the advent of the internet, e.g. access to technology (affordability and availability, including the issue of electricity in developing nations), user motivation and skill in using these new gadgets still stand. This edition, jointly produced with University of the South Pacific media staff, publishes a series of articles addressing these issues. On Media Freedom Day, 3 May 2006, the Fiji Media Council, assisted by USP’s regional journalism programme, organised a panel on ‘Media and alleviation of poverty’. The panel—men from the developed world who were either connected to the media industry in Fiji, or owned a great stake in it—talked about everything but the media’s role in alleviating poverty.